TOTEM AMBON MANISE:MEMBONGKAR SEGREGASI TERITORIAL BERBASIS AGAMA DI KOTA AMBON - Resa Dandirwalu (Antropologi Indonesia, 2014)
This writing is an effort done by the writer to break up the religious segregation that is still continuing in Ambon City, the Capital of Moluccas. Since the Social conflict started in January 19, 1999, then continued in September 11, 2011, and May 15, 2012 the religious people who live in harmony has become a fragile living. The Data collected by the observation and interview technique. Observation was done to collect the data about the impacts of social conflict, especially on the reality of segregation based on religion background, while interview was done with the tradisional / cultural leaders and the citizens of Ambon (Moslems and Christians as well). They involved directly or indirectly in the social conflict and undergo its impacts. After that, the researcher collected and studied the written documents that related to the research topic. The impact of social conflict in January 19, 1999 and September 11, 2011 is the territorial segregation based on religion background. This situation still held by the people from the Christians and Moslems because of the safety and comfort reasons, also traumatic and psychological reasons. Durkheim’s theory on totem is used by the writer to explain that reality of segregation. So the theory become the concept to break up the segregation based on religion background which is happening in Ambon. Totem: Ambon Manise, is a concept or slogan that is very closed to the Molucans. Therefore, this concept or slogan can be a self image of Molucans communally, and can be a norm that able to change their point of view and the daily attitude. The attitude of respect each other, help each other, and trust each other, before the conflict in 1999, was very good and tightly held among the Molucans. Therefore if a member of community does not have this attitude, he/she known as people who have not the Molucan identity. So, the Totem Ambon Manise can be a new Totem for Molucans, especially for the modern Ambonesse here and now. Then the Totem can be a common self image to build up the people life communally in order to create the social cohesion without the religious, ras, and tribe walls. This new totem does not reduct the totems belong to the clans. Conversely, it enriches the clan totems that have been belonged to the people until now.Key words: segregation, social conflict, slogan, totem, Ambon Manise, pela, gandong.